The Potential Role of Mitochondrial Acetaldehyde Dehydrogenase 2 in Urological Cancers From the Perspective of Ferroptosis and Cellular Senescence - Zhu, Weizhen; Feng, Dechao; Shi, Xu; Wei, Qiang; Yang, Lu (Frontiers in Cell and Developmental Biology, 2022)
Overproduction of reactive oxygen species (ROS) and lipid peroxidation promote the tumorigenesis, and mitochondrial aldehyde dehydrogenase 2 (ALDH2) is associated with the detoxification of reactive aldehydes generated from ROS-mediated lipid peroxidation, such as 4-hydroxy-2-nonenal (4-HNE), malondialdehyde, and acrolein. ALDH2 has been demonstrated to be highly associated with prognosis and chemoradiotherapy sensitivity of many cancers, including lung cancer, leukemia, renal cell carcinoma, head and neck cancer, esophageal cancer, bladder cancer, hepatocellular cancer, pancreatic cancer, and ovarian cancer. In this study, we tried to explore possible relationship between ALDH2 and urological cancers from aspects of ferroptosis, epigenetic alterations, proteostasis, mitochondrial dysfunction, and cellular senescence.